Genetic Diversity, Chemical Constituents, and Bioactivities of Maerua siamensis from Thailand - Natthawadi Wongthet; Markus Bacher; Mara Krenn; Apichart Jai-aree; Thomas Rosenau; Patsakorn Tiwutanon; Nopparat Anantaprayoon; Srunya Vajrodaya; Lothar Brecker; Johann Schinnerl; Ekaphan Kraichak (Plants)
The genus Maerua (Capparaceae) comprises 85 woody species distributed across the paleotropics, with some species used in traditional medicine. This study investigated the phylogenetic placement, genetic diversity, and phytochemical composition of Maerua siamensis, a species native to Indochina. Phylogenetic analyses using matK and rbcL markers confirmed the monophyly of the M. siamensis specimens collected from Thailand. Population genetic analyses revealed low genetic diversity across the sampled populations, suggesting purifying selection or recent demographic events. Phytochemical investigations of the leaf extracts led to the isolation and identification of 12 compounds, including two novel structures: maeruamide and maeruaoside. The isolated compounds encompass simple phenolics, l-proline-derived betaines, and flavonoid glycosides. Bioactivity assays revealed moderate antioxidant activity of the crude extract (EC50 = 106 μg mL−1), but no significant insecticidal or nematocidal effects were observed. This study provides new insights into the genetic diversity, phytochemistry, and potential bioactivities of M. siamensis, contributing to our understanding of this understudied species and its ethnomedicinal applications.